PHYTOCHEMICAL INVESTIGATION OF THE MEDICINAL PLANT MORICANDIA ARVENSIS L. FROM ALGERIAN SAHARA - Berreghioua, Abdelaziz; Cheriti, Abdelkrim (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this research was to isolate and identify flavonoids extracted from the leaves of Moricandia arvensis. Methods: The phytochemical screening reaction and thin-layer chromatography have been used to characterize the chemical groups, before they were identified by nuclear magnetic resonance. Results: The leaves contain essentially flavonoids, tannins, cardenolides, saponins, and alkaloids. The phytochemical investigation of the water-acetone extract led to the isolation of five flavonoids derivatives, namely: 5,7-dihydroxy-3,6,4'-trimethoxyflavone (1); 5,7,4'-trihydroxy- 3,6,8,3'-tetramethoxyflavone (2); 3,3',4', 5,7- pentahydroxy flavanone (3); 3-glucosyl 3',4',5,7 tetrahydroxy flavonol (4); and kaempfÃ©rol-3- digalactopyranoside (5). The structures of 1â€“5 were identified by comparison of their spectral data with those reported in the literature. Conclusion: In this work, it was possible to isolate and identify five flavonoids after fractionation of the hydroacetone extract from the leaves of the medicinal plant M. arvensis.